Orality and the problem for its implementation in the civil process. Under a look at our original 1993 CPC - Rioja Bermúdez, Alexander (2020)
The present is a work that seeks to highlight the problems that appeared with the implementation of the Civil Procedure Code of 1993 which must be taken into account in this second stage of the orality of the civil process and avoid making the same mistakes again, allowing the implementation of the oral system in our legal reality to be more robust and more effective.